PWE-141 Impact of The 'Be Clear On Cancer' National Oesophago-Gastric Cancer Awareness Campaign on Endoscopy Services and Cancer Diagnosis Rates and Outcomes. (17th August 2016) - Kabir, M; Khoo, D
Abstract : Introduction: Previous regional pilot studies have suggested that media campaigns for upper gastrointestinal (UGI) cancers successfully increase public awareness of symptoms, increase two-week wait pathway (2 WW) general practitioner (GP) referrals and increase the numbers of cancers diagnosed. 1 This prompted the roll-out of a nationwide televised media campaign, which promoted dyspepsia as a sign of cancer, from 26 th January to 22 nd February 2015. This study aimed to evaluate its impact, which is not well known to date, on the numbers of GP referrals made to a high volume endoscopy unit in London and the numbers and prognosis of the cancers diagnosed. Methods: This was a retrospective observational study, analysing departmental and patient records at the Barking, Havering and Redbridge Hospitals NHS Trust. Total numbers of GP 'urgent' priority and 'two-week wait' (2 WW) cancer pathway referrals for UGI endoscopies were collected from a six month period before the onset of the campaign and compared with a six month period after the campaign onset. The total numbers, demographics and outcomes of the oesophago-gastric cancers referred and diagnosed in the pre- and post-campaign period were recorded. Student paired t tests and χ2 tests were used to assess for statistical significance. Results: There were 1143 urgent/2 WW UGI endoscopy referrals made by GP's in the pre-campaign period and 1448 referrals in the post-campaign period. There was a statistically significant rise of mean monthly 2 WW referrals in the post-campaign period by 36.5% (p = 0.001). The extra demand was most noticeable in the 2 month post-campaign period with a mean weekly referral rate increase of 46.5% (p = 0.001), equating to 20 extra UGI endoscopies requested per week. However, there was no statistically significant change in the overall rates of oesophago-gastric cancers detected in any age group (47 cancers pre-campaign vs. 38 post-campaign), in their staging or the proportion that could be treated with curative intent. Most of the cancers diagnosed in both groups actually presented as dysphagia (35–37%) and/or weight loss (22–27%) rather than dyspepsia (10–11%). Conclusion: The national oesophago-gastric cancer awareness campaign significantly increased the demand placed on endoscopy services but did not meet its aim of detecting more cancers at an earlier curative stage. Most diagnosed were still in advanced stages 3 and 4. Perhaps future campaigns should place more emphasis on promoting awareness of dysphagia, which was more strongly associated with cancer detection, in addition to dyspepsia, in order to increase cancer detection rates. Reference: 1 Cancer Research UK literature: http://naedi.org/beclearoncancer/oesophago-gastric Disclosure of Interest: None Declared